Liver-first strategy for a combined lung and liver transplant in patients with cystic fibrosis. (6th May 2021) - Aburahma, Khalil; Salman, Jawad; Engel, Bastian; Vondran, Florian W R; Greer, Mark; Boethig, Dietmar; Siemeni, Thierry; Avsar, Murat; Schwerk, Nicolaus; Müller, Carsten; Taubert, Richard; Hoeper, Marius M; et al.
Abstract: : OBJECTIVES: A combined lung and liver transplant in patients with cystic fibrosis (CF) is an uncommon procedure. The goal of this study was to compare long-term outcomes between patients with CF who underwent either a combined lung-liver or a lung-only transplant. METHODS: This is a retrospective single-centre study of patients with CF who underwent a lung transplant between January 2005 and May 2020. Since 2006, our preference for a combined lung-liver transplant was to transplant the liver first and then the lung. Outcomes were compared using the Kaplan–Meier analysis and the log-rank test. Median follow-up was 53 (23–97) months. RESULTS: During the study period, among 357 patients with CF who underwent a lung transplant, 14 (4%) required a lung-liver transplant whereas 343 (96%) had a lung-only transplant. Lung cold ischaemic time was longer in the lung-liver transplant group, but no patient in this group showed primary graft dysfunction at 72 h after the transplant. Prevalence of anti-human leucocyte antigen donor-specific antibodies was 7.1% vs 13.7% in the lung-liver versus the lung-only transplant group ( P = 0.42). At 5 years, lung graft survival (78% vs 69%) and freedom from chronic lung allograft dysfunction (79% vs 62%) did not differ between the lung-liver versus the lung-only groups ( P = 0.45 and P = 0.55, respectively). Freedom from lung biopsy-confirmed rejection was significantly higher in patients undergoing a lung-liver transplant (91% vs 50%; P = 0.027). CONCLUSIONS: A lung-liver transplant did not impair lung graft function. The lower prevalence of donor-specific antibodies and the better freedom from lung biopsy-confirmed rejection suggest tolerogenic effects of the liver graft.